Legitimacy without members? Hungarian lessons on how to guarantee trade union representativeness. - Gyulavári, Tamás; Kártyás, Gábor (International Labour Review, 2026)
The article focuses on the challenges and legal framework surrounding trade union representativeness and collective bargaining in Hungary. It highlights Hungary’s low and declining collective bargaining coverage—below 20 percent—and trade union density, attributing much of this trend to restrictive labour law provisions introduced notably in the 2012 Labour Code reform. The authors analyze Hungarian statutory rules on representativeness, including the 10 percent membership threshold for unions to conclude collective agreements, the requirement for unanimous consent among multiple unions, and the limited role of works councils as substitutes for unions, arguing these create significant barriers to effective collective bargaining. The article also discusses the near absence of sectoral-level bargaining and severe restrictions on collective bargaining rights in the public sector, particularly in healthcare, contrasting Hungarian practice with ILO standards and other European models. It concludes with reform proposals aimed at expanding collective bargaining coverage by allowing employee representatives to negotiate agreements, harmonizing sectoral representativeness criteria, and extending collective bargaining rights in the public sector, emphasizing that these lessons may be relevant for other Eastern European and post-socialist labour markets with low union density.